2000
DOI: 10.1002/1529-0131(200011)43:11<2543::aid-anr23>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Sex and site differences in cartilage development: A possible explanation for variations in knee osteoarthritis in later life

Abstract: Objective. To test the hypothesis that sex-related and joint compartment-related differences in the risk of osteoarthritis (OA) of the knee might be associated with variations in cartilage development, we investigated knee cartilage volume in healthy children. Methods. We studied 92 children who were randomly selected from among students in grades 3-12 of a single school in Hobart, Tasmania (49 boys, 43 girls; age range 9-18 years). Articular cartilage thickness and volume were determined at the patella, media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

15
275
2
5

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 244 publications
(297 citation statements)
references
References 18 publications
15
275
2
5
Order By: Relevance
“…If symptomatic OA was present in both knees, the knee with less severe OA as determined radiographically was studied. The patients' knees were imaged in the sagittal plane on a 1.5T whole-body MR unit (Sigma Advantage GE Medical Systems; Milwaukee, WI) with use of a commercial receive extremity coil as previously described (3,4). The method to transform the images to the coronal plane has also been described previously (5).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…If symptomatic OA was present in both knees, the knee with less severe OA as determined radiographically was studied. The patients' knees were imaged in the sagittal plane on a 1.5T whole-body MR unit (Sigma Advantage GE Medical Systems; Milwaukee, WI) with use of a commercial receive extremity coil as previously described (3,4). The method to transform the images to the coronal plane has also been described previously (5).…”
Section: Methodsmentioning
confidence: 99%
“…The method is reproducible, with coefficients of variation (CVs) of ϳ2% (2-4). This technique has been used to explore factors that influence knee cartilage in healthy adults and children (3,4).…”
mentioning
confidence: 99%
“…In conjunction with state-of-the-art three-dimensional (3D) postprocessing tools (qMRI) the technique has been shown to produce accurate and precise data on the cartilage morphology (volume, thickness, and surface area) of the knee in healthy individuals (Stammberger et al, 1999a;Hohe et al, 2002), and in patients with femorotibial osteoarthritis (OA) (Burgkart et al, 2001). Various studies have revealed that the knee-joint cartilage volume displays a high intersubject variability (Eckstein et al, 1998a(Eckstein et al, , 2001aCicuttini et al, 1999;Jones et al, 2000), but little is known about the determinants of this variability. Several authors (Karvonen et al, 1994;Cova et al, 1996;Dalla Palma et al, 1997;Eckstein et al, 1998aEckstein et al, , 2001aCicuttini et al, 1999;Jones et al, 2000) have investigated the correlation of knee-joint cartilage morphology with anthropometric variables such as body height, body weight, and age.…”
mentioning
confidence: 99%
“…Various studies have revealed that the knee-joint cartilage volume displays a high intersubject variability (Eckstein et al, 1998a(Eckstein et al, , 2001aCicuttini et al, 1999;Jones et al, 2000), but little is known about the determinants of this variability. Several authors (Karvonen et al, 1994;Cova et al, 1996;Dalla Palma et al, 1997;Eckstein et al, 1998aEckstein et al, , 2001aCicuttini et al, 1999;Jones et al, 2000) have investigated the correlation of knee-joint cartilage morphology with anthropometric variables such as body height, body weight, and age. Body height and weight have been shown to be only weakly correlated with cartilage volume (Dalla Palma et al, 1997;Eckstein et al, 1998a;Cicuttini et al, 1999;Jones et al, 2000), and in particular with cartilage thickness (Karvonen et al, 1994;Eckstein et al, 2001a).…”
mentioning
confidence: 99%
See 1 more Smart Citation